Decomposition and phosphorus release of agroforestry shrub residues and the effect on maize yield in acidic soils of Rubona, southern Rwanda - Mukuralinda, Athanase; Tenywa, J.S.; Verchot, Louis V.; Obua, J.; Namirembe, S. (2009)
Phosphorus release from decomposing leaf biomass of Calliandra calothyrsus Meissner, Tithonia diversifolia Hensley A.Gray and Tephrosia vogelii Hook.f. agroforestry species applied alone or combined with triple super phosphate (TSP) was studied at World Agroforestry Centre (ICRAF) laboratory for 56 days using an incubation method. The effects of above treatments on maize yield were evaluated in the field at Rubona, southern province of Rwanda between the years 2001 and 2004. The net cumulative phosphorus (P) mineralised ranged from 16.2 to 212.2 mg P kg-1. The net P mineralisation rates from green manure, TSP applied alone or combined with green manure decreased in the order green manure > green manure + TSP > TSP > lime > control. The best plant residues quality for predicting P mineralisation is total P, C, and C:P & C:N ratios. Relative to the control, leaf biomass combined with TSP resulted in six times higher maize grain yield at the end of the experiment i.e., from 0.9 to 7.1 t ha-1. In the fourth season, application of Tithonia diversifolia Hensley A.Gray green manure combined with TSP at 50 kg P ha-1 resulted in higher maize yield (25% increase) than TSP and Tithonia diversifolia Hensley A.Gray (9% increase) applied alone at the similar rate. Therefore, application of plant residues and TSP alone might not be sufficient to meet maize plant P requirements and to achieve the yield potential of maize in the Rubona soils unless supplemented with mineral fertilisers.